Development of two diatom‐based indices: a biotic and a multimetric index for assessing mine impacts in New Zealand streams - KA Schowe; JS Harding (New Zealand Journal of Marine and Freshwater Research, 2014)
Diatoms are widely recognised as potentially useful biological indicators, and are increasingly incorporated into water quality monitoring in North America and Europe. Despite their potential there have been no diatom‐based indices developed for New Zealand. Overseas, diatoms have been shown to be especially useful in the monitoring of acid mine drainage (AMD). We sampled diatoms from 39 streams along an AMD gradient on the West Coast of the South Island, New Zealand. We developed two indices from relative abundance data; a single biotic index (pHBI) and a multimetric index (Diatom Mine Pollution Score [DMPS]). Both indices were able to categorise streams as circum‐neutral, moderately or severely impacted by AMD. However, neither index was able to differentiate naturally acidic streams (pH 4.0–5.7) from those moderately impacted by AMD. Diatom species responded to changes in acidity but were less affected by metals. Overall, this study demonstrates the potential usefulness of diatoms in monitoring the impacts of AMD, specifically acidity, in New Zealand streams.